The value of knowledge and the pursuit of understanding - Kvanvig, Jonathan L. (Cambridge studies in philosophy., 2003)
Jonathan Kvanvig argues that epistemology cannot ignore the question of the value of knowledge and questions the assumption that knowledge is always more valuable than the value of its subparts. Clearly written and well argued, the book will appeal to students and professionals in epistemology.